Morphological, ecological and toxicological aspects of Raphidiopsis raciborskii (Cyanobacteria) in a eutrophic urban subtropical lake in southern Brazil - Werner, Vera Regina; Tucci, Andréa; da Silva, Lisangela Marques; Yunes, João Sarkis; Neuhaus, Emanuel Bruno; Berthold, David E.; Laughinghouse IV, H. Dail (Iheringia, Série Botânica., 2020)
A dense perennial bloom of Raphidiopsis raciborskii was observed in an urban lake (29°53’13”S and 51°09’29.9”W). Due to supposed toxicity, this study analyzed the morphology of the species, evaluated the main factors that influence its growth, and examined bloom toxicity. Two sites were sampled monthly from November 2009 to November 2010. The species was found in all samples and dominated in 77% of the samples. Highest density was recorded at the end of summer (March – 199,550 ind.mL-1) at 26.6 ºC and pH 7.8. High densities were also found at low temperatures (72,145 ind.mL-1 at 12.6 °C and 130,475 ind.mL-1 at 14.5 °C) and at minimum (5.4) and maximum (8.7) pH, reaching 89,964 ind.mL-1 and 61,400 ind.mL-1, respectively. Nitrogen availability was high, especially ammonium [(60-)140-660 μg.L-1], and phosphorus was low (orthophosphate < 10 μg.L-1). These results support that R. raciborskii has a wide tolerance to abiotic variations. Saxitoxins and gonyautoxins were found in the bloom